Blockchain-IoT supply chain: systematic literature review - Umi Nabilah Badrol Said; Mohd Rizuan Baharon; Mohd Zaki Mas’ud; Ariff Idris; Noor Azurati Ahmad Salleh (Universitas Ahmad Dahlan, 2023)
Since 2016, the implementation of blockchain in the supply chain has attracted wide interest among researchers. The creation and study of blockchain technology have grown at an exponential rate in the last decade. The supply chain would be a massive technological leap with the combination of blockchain technology that brings major changes to different facets of the industry, such as record immutability, improved traceability, quality assurance, improved knowledge flows, decentralized power structure, and decreased chances of fraud. With the growth in blockchain Internet-of-Thing (IoT) supply chain technologies, the security risk of implementing such technologies and methods to counter it has been largely discussed among researchers. This study analyses peer-reviewed literature attempting to use authentication in the blockchain-IoT supply chain to counter security risks in the technologies and provides a comprehensive analysis of the important feature when creating an authentication technique for the blockchain-IoT supply chain. Finally, the study discusses some of the problems and research objectives in the realm of authentication in the blockchain-IoT supply chain.